2020
DOI: 10.1111/dth.13988
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications and role of serum sphingolipids on psoriasis severity after narrow band ultraviolet B treatment: A cross sectional controlled study

Abstract: Sphingolipids (SLs), are structural components of the skin that contribute to the regulation of the proliferation and differentiation of keratinocytes as well as regulation of the skin epidermal barrier. A prospective cross sectional comparative controlled study was designed to evaluate the serum level of sphingosine 1 phosphate (S1P) and ceramide (CER) before and after narrow band ultraviolet B (NBUVB) in psoriatic patients. The study included 32 patients presented with psoriasis and 32 healthy age and sex ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, a statistically significant positive correlation was identified between the severity of psoriasis and the serum levels of sphingosine-1-phosphate both before and after treatment with narrow-band ultraviolet B (NBUVB) therapy (r = 0.374, p = 0.003). However, no significant correlation was found between disease duration or patient age and sphingosine-1-phosphate levels (r = 0.393, p = 0.765) [21]. This suggests that sphingosine-1-phosphate serum levels may serve as a potential marker for assessing the severity of psoriasis and monitoring the effectiveness of NBUVB treatment.…”
Section: The Role Of Sphingosine-1-phosphatementioning
confidence: 85%
“…Furthermore, a statistically significant positive correlation was identified between the severity of psoriasis and the serum levels of sphingosine-1-phosphate both before and after treatment with narrow-band ultraviolet B (NBUVB) therapy (r = 0.374, p = 0.003). However, no significant correlation was found between disease duration or patient age and sphingosine-1-phosphate levels (r = 0.393, p = 0.765) [21]. This suggests that sphingosine-1-phosphate serum levels may serve as a potential marker for assessing the severity of psoriasis and monitoring the effectiveness of NBUVB treatment.…”
Section: The Role Of Sphingosine-1-phosphatementioning
confidence: 85%
“…serum is altered in psoriasis patients; the total ceramide level decreases, and the serum S1P level increases, in severe psoriasis patients [107,108]. A cross-sectional controlled study also showed an increase in the serum S1P level and a decrease in the serum ceramide level in psoriasis patients and a positive correlation between the psoriasis severity and serum S1P levels [109]. Moreover, the serum S1P level is lower in obese psoriasis patients (BMI > 30) compared to in normal-weight patients (BMI < 30) [110] (Figure 2).…”
Section: Sphingolipids In Psoriasismentioning
confidence: 93%
“…Several studies have found higher serum or plasma levels of S1P in patients with psoriasis [118][119][120], AR [121][122][123], and asthma [112, 124,125], the latter being correlated with the severity of the disease and a worse response to the treatment [124]. Additionally,…”
Section: Sphingolipidsmentioning
confidence: 99%
“…Several studies have found higher serum or plasma levels of S1P in patients with psoriasis [118–120], AR [121–123], and asthma [112, 124, 125], the latter being correlated with the severity of the disease and a worse response to the treatment [124]. Additionally, activation of S1P pro‐inflammatory signalling pathways through the sphingosine kinases (SphKs), S1P and S1P receptors (S1PRs) axis has been extensively characterised in ulcerative colitis (UC) patients and animal models [126, 127].…”
Section: Inflammatory Mechanismsmentioning
confidence: 99%